ChemInform Abstract: A Stereoselective Cyclization Strategy for the Preparation of γ‐Lactams and Their Use in the Synthesis of α‐Methyl‐β‐proline. Issue 23 (16th May 2013) - Banerjee, Souvik; Smith, Justin; Smith, Jillian; Faulkner, Caleb; Masterson, Douglas S.
Abstract The reaction of benzyl malonic esters with hydrazine allows a convenient and stereoselective access to the (R)‐γ‐lactam (IV).